Acoustic sensors for biomedical applications - Dey, Nilanjan 1984- (SpringerBriefs in speech technology studies in speech signal processing, natural language understanding, and machine learning series / editor, Amy Neustein, 2019)
In this book, application-related studies for acoustic biomedical sensors are covered in depth. The book features an array of different biomedical signals, including acoustic biomedical signals as well as the thermal biomedical signals, magnetic biomedical signals, and optical biomedical signals to support healthcare. It employs signal processing approaches, such as filtering, Fourier transform, spectral estimation, and wavelet transform. The book presents applications of acoustic biomedical sensors and bio-signal processing for prediction, detection, and monitoring of some diseases from the phonocardiogram (PCG) signal analysis. Several challenges and future perspectives related to the acoustic sensors applications are highlighted. This book supports the engineers, researchers, designers, and physicians in several interdisciplinary domains that support healthcare.